Late Holocene climate reorganisation and the North American Monsoon - Jones, Matthew D.; Metcalfe, Sarah E.; Davies, S.J.; Noren, A. (Elsevier, 2015)
The North America Monsoon (NAM) provides the majority of rainfall for central and northern Mexico as well as parts of the south west USA. The controls over the strength of the NAM in a given year are complex, and include both Pacific and Atlantic systems. We present here an annually resolved proxy reconstruction of NAM rainfall variability over the last ~6ka, from an inwash record from the Laguna de Juanacatlán, Mexico. This high resolution, exceptionally well dated record allows changes in the NAM through the latter half of the Holocene to be investigated in both time and space domains, improving our understanding of the controls on the system. Our analysis shows a shift in conditions between c. 4 and 3 ka BP, after which clear ENSO/PDO type forcing patterns are evident.